Sythesis and characterization of silver nanoparticles stabilized in extract of Struthanthus flexicaulis Mart. (birdweed) (Research, Society and Development, 2021)
The synthesis of silver nanoparticles is a growing area in nanotechnology. The green synthesis has achieved space and recognition in the scientific community, according to the guideline of the environmentally correct. The present work aimed to synthesize and characterize silver nanoparticles stabilized in Struthanthus flexicaulis Mart. Synthesized AgNPS were confirmed by the presence of visible plasmonic band spectrum in the range between 430nm to 480nm. The Zeta potential measurements for the three produced species, AgNPS-I, AgNPS-D and AgNPS-M ranged from -28.0 mV to -22.0mV, indicating particles as unstable or neutral. The Polydispersity index (PDI) was between 0.296 and 0.303 showing homogeneity in the samples, low variation in particle sizes, and no aggregates. The diameter size of the AgNPS formed was between 45nm and 60nm, which demonstrates a surface modification of the products formed. The synthesis of AgNPS from the green synthesis showed a desirable equivalence between the results, which will add to future studies on Struthanthus flexicaulis Mart, that has been used for therapeutic purposes.